Exposure and risk analysis to particulate matter, metals, and polycyclic aromatic hydrocarbon at different workplaces in Argentina - Colman Lerner, Jorge Esteban (2018)
In order to estimate air quality at work environments from small and medium-sized enterprises (SMEs), we determined both the concentration of particulate matter (PM10 and PM2.5) and the presence of polycyclic aromatic hydrocarbons (PAHs), as the heavy metals in the composition of the particulate matter. Three SMEs located in the city of La Plata, Argentina, were selected: an electromechanical repair and car painting center (ERCP), a sewing work room (SWR), and a chemical analysis laboratory (CAL). The results evidenced high levels of PMexceeding the limits allowed by the USEPA and the presence of benzo(k)fluoranthene in all the analyzed sites and benzo(a)pyrene in the most contaminated site (ERCP). Regarding metals, the presence of Cd, Ni, Cu, Pb, and Mn, mainly in the fraction of PM2.5, in the same workplace was found. As far as risk assessment at all the workplaces surveyed is concerned, risk values for contracting cancer throughout life for exposed workers (LCR) did not comply with the parameters either of USEPA or of WHO (World Health Organization).